Analisis dan Pengembangan Teknik Auto Lipsync Pada Divisi Produksi Animasi 2D di MSV Studio - Kristama, El Johan; Suyanto, M.; Al Fatta, Hanif (Politeknik Indonusa Surakarta, 2023)
The influence of the pipeline in the 2D animation industry greatly affects the animation production process to be effective and efficient so that it can produce good animation but with minimal effort. MSV Studio itself has several divisions in the production process, one of which is the animation production division. In producing a 2-dimensional animated film in which there are many conversation scenes, mouth movements are needed that match the voice or character dialogue. With the auto lipsync technique, animating mouth movements that match the dialogue can be done quickly and accurately so as to cut animation production time efficiently. This study provides an overview of how the mouth movement animation of a 2-dimensional character is created and can move automatically according to the sound entered into the software, compared to mouth movement animations that are created or drawn manually one by one. In the end, this study can be a reference in making mouth movement animations in 2D animated films, and can be developed again in the future.